Pengaruh Terpaan Informasi Vlog di Media terhadap Sikap Guru dan Dampaknya terhadap Persepsi Siswa - Nur Kholisoh (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
In today’s digital era, more and more information is delivered through social media, one of which is vlog which is currently a trend among high school students. Teacher as one of the main educators for high school students is still underestimate the content of social media. Teachers are more concerned about negative impact of social media. This study aims to determine the impact of information in the media on students’ perceptions of social media (vlog) content, the impact of media information on teacher attitudes, and the impact of teacher attitudes on high school students’ perceptions of vlog. This research uses a positivist paradigm with survey method by using path analysis. The result shows that (1) the information exposure in the media has influenced the attitudes of the teachers, (2) the information exposure in the media has influenced the perception of high school students, and (3) the attitude of teachers also has influenced the perception of high school students about the content in social media (vlog).